2015
DOI: 10.1589/jpts.27.149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isometric exercise using biofeedback on maximum voluntary isometric contraction, pain, and muscle thickness in patients with knee osteoarthritis

Abstract: [Purpose] The purpose of our study was to investigate the effects of isometric exercises using electromyographic biofeedback (EMGBF) and ultrasound biofeedback (USBF) on maximum voluntary isometric contraction (MVIC), pain assessed by the Visual Analogue Scale (VAS), and vastus medialis oblique (VMO) thickness in patients with knee osteoarthritis (OA). [Subjects and Methods] Thirty females over 65 years of age who had been diagnosed with knee osteoarthritis were recruited and randomly assigned to three groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 47 publications
1
43
1
3
Order By: Relevance
“…Only the EMGBF training group showed significantly increased VMO thickness compared with before training. 33 The results of that study are against our finding that VMO thickness did not change by EMGBF. This may be attributed to the different method of measuring VMO thickness applied in Choi et al…”
Section: Discussioncontrasting
confidence: 59%
“…Only the EMGBF training group showed significantly increased VMO thickness compared with before training. 33 The results of that study are against our finding that VMO thickness did not change by EMGBF. This may be attributed to the different method of measuring VMO thickness applied in Choi et al…”
Section: Discussioncontrasting
confidence: 59%
“…In previous studies, many studies have reported the use of EMG biofeedback in the treatment of LBP by relaxation training of para vertebral muscles [13,14]. In the last few years, the use of EMG feedback as an adjunctive to the standard exercise regime for increasing muscle strength has been investigated in several studies [15,16]. Many studies reported the add on effects of EMG biofeedback in various relaxation training to reduce the standing level of para vertebral muscle tension and exercise program to strengthen the back muscles [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It is now well-established that finding an anatomical reference axis is crucial for femoral component rotational alignment, by which, osteotomy for the distal femoral epicondyles and posterior condyles can be correctly carried out and component can be correctly placed 2 ) . At present, at least 4 references are being used to determine the rotational alignment of the femoral component in clinical practice: 3° external rotation of the posterior femoral condyles, Whiteside’s line (the perpendicular line of the distal femoral anterior-posterior (AP) axis in the frontal plane), the femoral epicondylar axis, and the femoral component rotational angle when the knee flexion space is rectangularly shaped in ligament balancing 3 ) . Of the four references, the first one has been most widely used.…”
Section: Introductionmentioning
confidence: 99%